Increasing Family Awareness of COVID-19 Transmission In Vulnerable Communities - Iche Andriyani Liberty; Fikri, Muhammad Zainal; Irfani, Tri Hari; Pariyana, Pariyana; Tjekyan, Suryadi (CV. Inara, 2021)
COVID-19 cases in Indonesia are still quite high. However, community mobility continues to increase. If in a family there is a vulnerable and / or comorbid age group, it will certainly be increasingly threatened when a productive family member leaves the house but is negligent in implementing health protocols. People who live in market areas, of course, are in direct contact with high economic activities and of course also indicate high mobility. The purpose of this activity is to increase family awareness of COVID-19 transmission in vulnerable communities with comorbidities. The target audience for this community service activity is 31 people who live in the Jakabaring Main Market area of ​​Palembang City. This community service activity results in an increase in knowledge about the importance of health protocols that are carried out in a disciplined and correct manner. This health protocol is carried out in order to protect each other starting from the family and for the community, especially for vulnerable communities. Apart from home visiting activities, the construction of hand washing facilities will also be used by the surrounding community and at the same time become a symbol to remind that washing hands with soap in running water is not only an obligation of the health protocol for preventing COVID-19 but will also save many lives from various threats of other infectious diseases.